Zuhud in Modern Sufism: Bridging Spirituality and Economic Life - Muhammad Fahrurrozi; Siswoyo Aris Munandar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to explore the concept of zuhud within the perspective of modern Sufism and its application to economic life. The authors’ interest in this research stems from the traditional and widespread understanding of zuhud as the practice of renouncing worldly pleasures to draw closer to God. However, its interpretation has evolved within a more dynamic modern context. Consequently, the authors seek to demonstrate that the teachings of zuhud do not necessarily require abandoning worldly possessions or living in poverty. The study employs a qualitative methodology with a descriptive-analytical approach, including a literature review of Qur’anic verses related to zuhud and interpretations from contemporary Sufi scholars. The findings reveal that zuhud in modern Sufism is no longer regarded as an extreme ascetic practice but as a balanced perspective that integrates spirituality and materiality. In the economic sphere, zuhud is interpreted as a work ethic emphasizing honesty, justice, and the use of wealth for communal benefit. This research makes a significant contribution to understanding the integration of the spiritual values of zuhud within modern economic life. It provides fresh insights for economic practitioners and Sufi enthusiasts in applying spiritual principles to everyday life. Furthermore, the study highlights several modern Sufi figures who advocate for the concept of zuhud without promoting a life of poverty. These figures serve as examples of how zuhud can manifest in economic and entrepreneurial activities.